Trabajo en equipo y productividad en la Municipalidad Provincial de Alto Amazonas 2025 - Linares Cancino, Ramfor (2025)
The study aimed to determine the relationship between teamwork and productivity in the Provincial Municipality of Alto Amazonas, 2025. A basic methodology was used, with a descriptive correlational approach and a non experimental design. The study population consisted of 75 collaborators. The results showed that teamwork is average, reaching 28%. This assessment is due to the fact that there is almost always a leader accepted by all. Productivity was also average, at 24%. This is because collaborators occasionally share their work knowledge for the benefit of their colleagues. Finally, it was determined that there is a positive and significant relationship between teamwork and productivity, with a compensation coefficient of 0.758 and a significance level of 0.000. Likewise, skills were identified as having a coefficient of 0.608 and a significance level of 0.000; The common purpose coefficient was 0.660 and a p-value of 0.000; while the internal norms coefficient was 0.651 and a significance level of 0.000. These results confirm the existence of statistically significant relationships between the different dimensions of teamwork and work productivity.